(3GJMGa GdHQQI HeG ScJ Yf fTQ GdYTQIs - (3oeUWai Hf YHO GdQMef GdCQVhj GdTgjQ HGdCRejQjs; (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO GHf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s
(3ChdgG (B:s
(3hHYO bGd GdYHO GdabjQ eUWai GdTgjQ HGdCRejQi gPG HjGf eG WYf Hg Gdbde heG Cgedg aj cJGHg GdoeSei s
(3BNQgG (B:s
(3hdGJMSHf aj GdShQJjf HGdNWGH hEPf aj GdML HaJM GdgeRI ef GdeUjGM JeJ s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B174s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1953s
Keywords: (3GdbQGAGJ hGdJLhjOs